Attitude Of Teachers Towards Inclusive Education In Relation To Their Perceived Self-Efficacy To Teach In Inclusive Classroom - Bala, Dr Indu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Inclusive Education is the education which is provided to the special needs and general students in the same roof with the special support devices or services. This paper aims to look upon the concept of inclusive education in general. The central purpose of the paper is to find the Teachers’ attitude towards inclusive education in relation to their perceived self-efficacy to teach in inclusive classroom. For the present study a sample of 50 teachers of government schools were drawn by using simple random sampling method. The study is delimited to the Jalandhar district only. Findings of the study were; a total of 24% of teachers were having positive attitude (overall), 62% showed neutral attitude (overall) and 14% of teachers were found with negative attitude (overall) towards inclusive education. Also, a total of 12% of teachers were found to have positive efficacy (overall), 76% of teachers have neutral efficacy (overall) and 12% teachers have negative overall perceived efficacy to teach in inclusive classroom. Teachers’ attitude towards inclusive education was found positively correlated with perceived self-efficacy to teach in inclusive classroom.